Zines in Third Space : Radical Cooperation and Borderlands Rhetoric - Licona, Adela C. (Book collections on Project MUSE., 2012)
"Zines in Third Space develops third-space theory with a practical engagement in the subcultural space of zines as alternative media produced specifically by feminists and queers of color. Adela C. Licona explores how borderlands rhetorics function in feminist and queer of-color zines to challenge dominant knowledges as well as normativitizing mis/representations. Licona characterizes these zines as third-space sites of borderlands rhetorics revealing dissident performances, disruptive rhetorical acts, and coalitions that effect new cultural, political, economic, and sexual configurations."